A Translation Analysis Of Noun Phrase In Inside The Kingdom's Novel By Carmen Bin Ladin And Its Translation - Pratiwi, Yeni (2012)
The objectives of the study are to classify the translation shift of noun phrase and to describe the equivalent translation of noun phrase in Inside the Kingdom's novel by Carmen Bin Ladin. This research belongs to a descriptive qualitative study which takes a document oriented as the method of collecting data. By this method the writer uses translation done by Inside the Kingdom's novel by Carmen Bin Ladin as the data source, and the data taken are sentences that containing noun phrase which happened translation shift. As the comparison, there is the translation between English and Indonesian. The results of the research show that firstly, the translation shift is divided into 2 types: level shift (noun phrase are translated into adjective and verb) and structural shift of noun phrase (noun phrase are translated into prepositional phrase, adjective phrase, verb phrase, and noun phrase are omitted). Secondly, the translation is equivalent and non-equivalent translation. The level shift of noun phrase cover around 10 data or 20,8 % where as the structural shift of noun phrase cover around 38 data or 79,2 %. Lastly, there are 32 data or 66,6 % equivalence translation and 16 data or 33,4 % non-equivalence translation.